Ambipolar polymers for transistor applications. Issue 4 (6th April 2020) - Zhu, Xin; Zhang, Shi‐Rui; Zhou, Ye; Han, Su‐Ting
Abstract: In this mini‐review, we mainly discuss recent progress in polymeric semiconductors for ambipolar organic field‐effect transistors. The relationship between the device performance and the thin film microstructure, the molecular design as well as the processing conditions has been exemplified by several popular polymers such as diketopyrrolopyrrole, isoindigo and pyridal[2, 1, 3]thiadiazole, which will be reviewed and described. The thin film microstructure, the molecular design as well as the processing conditions have significantly influenced the performances of the devices. © 2020 Society of Chemical Industry Abstract : In this review, several kinds of polymeric semiconductors for ambipolar transistors will be introduced. The thin film microstructure, molecular design as well as processing conditions have significantly influenced the performance.